Suplementación con sulfato ferroso, alimentos fuentes de hierro y anemia ferropénica en niños de 6 a 35 meses del centro de salud San Juan de Miraflores 2023 - Guevara Silvano, Alexandra (2025)
The objective of the research was to determine the relationship between supplementation with ferrous sulfate and foods that are sources of iron and iron deficiency anemia in children aged 6 to 35 months at the San Juan de Miraflores Health Center. The study was descriptive and correlational, non experimental and quantitative, cross-sectional. The sample was made up of 120 children from 6 to 35 months of age treated and with a preventive and therapeutic scheme provided by the San Juan de Miraflores health center. The information was extracted from the medical records, the mothers also filled out a questionnaire and the children were evaluated with a hemoglobin measurement at the end of the supplementation regimen. 62.50% of those evaluated had a preventive supplementation scheme and 37.50% had a therapeutic anemia scheme. 98.33% had a low consumption of foods that were sources of iron, 1.67% had a medium consumption and 0% had a high consumption of foods that were sources of iron during the time of preventive or therapeutic supplementation. 51.67% had a normal hemoglobin level after complying with the preventive or therapeutic scheme of ferrous sulfate provided at the San Juan de Miraflores Health Center, 26.67% mild anemia and 21.67% moderate anemia. A significant statistical relationship was found between foods that are sources of iron with iron deficiency anemia and a highly significant relationship between supplementation with ferrous sulfate and iron deficiency anemia.